ANALISIS KINERJA BIDAN DESA DALAM MEMBERIKAN PELAYANAN KESEHATAN IBU DAN ANAK DI KABUPATEN TAPANULI UTARA - Emilia Silvana Sitompul (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2020)
The purpose of the research was to analyze the organizational factors with the performance of village midwives in providing maternal and child health services. The research type of quantitative method is analytic research with cross sectional approach. Research population of all village midwives who served in 5 (five) working areas of Puskesmas in North Tapanuli Regency. The sample of research using total sampling method as many as 120 people. Instrument of data collection used questionnaire. Data analysis used univariate analysis, bivariate with chi square test. The results showed that there was a relation between leadership (p <0.001), incentive (p <0.001) with village midwife performance in providing maternal and child health services. It is expected that the District Health Office of Tapanuli Utara District, in order to increase the incentives of the village midwife so that the village midwife is satisfied with adequate incentives and can show good performance in providing maternal and child health services